SAE Technical Paper Series 2015
DOI: 10.4271/2015-01-2138
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of Non-Spherical Particle Evolution for Ice Crystals Simulation with an Eulerian Approach

Abstract: In this study a comparison is made between results from three Eulerian-based computational methods that predict the ice crystal trajectories and impingement on a NACA-0012 airfoil. The computational methods are being developed within CIRA (Imp2D/3D), ONERA (CEDRE/Spiree) and University of Twente (MooseMBIce). Eulerian models describing ice crystal transport are complex because physical phenomena, like drag force, heat transfer and phase change, depend on the particle's sphericity. Few correlations exist for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…For this benchmark, a comparison with the results obtained with the Eulerian computational methods from CIRA and ONERA has been presented by Iuliano et al [63]. From this comparison it has been concluded that the general agreement between the collection efficiency results is very good.…”
Section: Haic Benchmark On Effect Particle Sphericitymentioning
confidence: 90%
“…For this benchmark, a comparison with the results obtained with the Eulerian computational methods from CIRA and ONERA has been presented by Iuliano et al [63]. From this comparison it has been concluded that the general agreement between the collection efficiency results is very good.…”
Section: Haic Benchmark On Effect Particle Sphericitymentioning
confidence: 90%
“…The expressions governing the motion, mass transfer, heat transfer and phase change need to be modified such that the effect of their shape is explicitly taken into account. These extensions were described previously for both Lagrangian [18,19] and Eulerian methods [20][21][22][23]. In this section the trajectory models are briefly described to underline the specifics of each approach.…”
Section: Ice Crystal Trajectoriesmentioning
confidence: 99%
“…Physical models -HAIC sub-project 6, which was devoted to models and tools development, made significant progress in the understanding of physical phenomena controlling ice crystal icing and led to the creation of a first generation of ICI models. All these models were implemented in 2D numerical research tools [13,16,21,22,26,29,32] for the purpose of empirical constant calibration and first level validation (i.e. based on academic configurations that are well-instrumented but only partially representative of real industrial applications).…”
Section: Existing Building Blocksmentioning
confidence: 99%
“…The second important innovation was the development of new numerical methods in particle trajectory & impact solvers to account for fragmentation phenomena and track secondary reemitted particles [15,26].…”
Section: Implementation Of An Ici Capability In Existing 3d Multidiscmentioning
confidence: 99%